Support Decision Tool for Sustainable Energy Requalification the Existing Residential Building Stock. The Case Study of Trevignano Romano - Fabrizio Cumo; Federica Giustini; Elisa Pennacchia; Carlo Romeo (Energies, 2020)
The control and improvement of energy-environmental quality in buildings are responsible for almost 40% of the emissions related to energy and processes, and are essential to achieve the commitment of the Paris Agreement and the Sustainable Development Goals (SDGs) United Nations (UN). This paper provides a support tool to planners and administrators of the territory for the identification of interventions aimed at the energy requalification of the existing Italian building heritage, mainly for residential use. The purpose of this tool is to reduce energy consumption by intervening on the building envelope with specific solutions that are identified through a matrix resulting from the study. In the first part of the study, an analysis was carried out on various factors such as the existing residential building, the building and construction types and the materials of the envelope typical of each construction period, which are critical for energy efficiency issues. In the second part of the study, the analysis of the state of the art of the insulating materials existing on the international and national market was carried out, in order to standardize the efficiency interventions of the building envelope. By exploiting the potential of the proposed matrix, and integrating it with Geographic Information System (GIS) technology, it would be possible to create a database containing information regarding the characteristics of the building envelope of the residential building stock and to identify a set of insulation interventions more suited to each specific case near Rome, Italy.